Analisis Tindak Tutur Lokusi Pada Unggahan Video Self Improvement Dalam Akun Instagram Hawaariyyun - Finda Rosita Dewi; Alifya Aenatul Nabila; Firli Safinah Az-zahroh; Anna Murdiyanti; Asep Purwo Yudi Utomo; Zuhrul Anam; Rossi Galih Kesuma (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This study investigates locutionary speech acts in self improvement videos on Hawaariyyun's Instagram account. Locutionary speech acts are speech acts that say something directly without other intentions. The subject of this research analysis is the use of locutionary speech acts in the self improvement video uploads of Hawaariyyun's Instagram account. This research uses descriptive qualitative approach as the methodology and pragmatics approach as the theoretical approach. The data source of this research is a fragment of speech on self improvement videos on Hawaariyyun's Instagram account. The data collection techniques in this research are listening technique and note-taking technique. The results of the analysis show that locutionary speech acts are often used by Hawaariyyun in his speech on self-improvement videos on his Instagram account. The results show that there are 31 locutionary speech acts, including 11 locutionary speech acts of news category, 9 locutionary speech acts of question category, and 11 locutionary speech acts of command category. This research can help readers in understanding locutionary speech acts. In addition, it is expected that this research can be useful for other writers as a reference regarding locutionary speech acts.